PENGARUH GAYA KEPEMIMPINAN KEPALA DESA TERHADAP DISIPLIN KERJA PELAKSANA PEMERINTAHAN DESA KARANGDORO KECAMATAN TEGALSARI KABUPATEN BANYUWANGI TAHUN 2011 - Baderun Baderun; Moh Suseno Suseno (Relawan Jurnal Indonesia, 2011)
The purpose of this study was to find out: (1) How is the leadership style applied by the Village Head; (2) What factors influence the application of the Village Chief's leadership style; (3) What is the influence of the Village Chief's leadership style on the discipline of implementing work in the Karangdoro village government. The population in this study was the number of all government executors of BPD, RT, RW, Village Institutions (LKMD, PKK, KT) Karangdoro Village Tegalsari District, Banyuwangi Regency . There are 2 (two) variables in this study, namely variable (X) is work discipline, variable (Y), namely leadership style. In this study using data collection methods through questionnaires, documentation. Based on the results of the study, it can be concluded: the leadership style of a village head has a positive relationship to the work discipline of his subordinates. This is evidenced by the acceptance of the hypothesis (Ha) indicated by the resulting -t value is 2.38> 2.048 which indicates that there is a positive relationship between leadership style and work discipline